A Santidade Enfurecida - Leandro Duarte Rust (Medievalista)
In the 11th century, Europe was marked by ecclesiastical conflicts. Although tensions between lay and clergy attracted, for more than a century, the largest share of the historians' attention - especially the so-called struggles between the priesthood and the empire -, the struggles between segments of the Church itself multiplied and intensified, achieving great documentary repercussion. Among the most frequent cases of disputes during the "Gregorian Reformation Era" were clashes between monks and bishops, whose outbreak had repercussions in numerous directions: on aristocratic domination, patrimonial control networks, foundations of ecclesiology, urban mobilizations, legal consensus. The following pages consist of a study of such a case: around 1034 a quarrel opposed the high echelon of the Florentine bishopric to a portion of local monasticism filling in decades with reports of terrifying miracles, popular clamours, open challenges to the papacy and bloody disputes by legal authority. The historical analysis of this conflict articulates chronicles, cartulars, epistolary and diplomatic, guided by the hypothesis that the field of action of agents would have been affected by a singular factor: the unveiling of certain emotions shifted the geography of public prerogatives.